Mortality inequality in Chile - Gede\~ao Locks (Fiscal Studies, 2024)
This paper analyses trends in mortality inequality in 330 Chilean communes from 1990 to 2010 for different age groups and both genders. Chile had substantial inequalities in local-level mortality rates in 1990 but by 2010 these disparities had significantly decreased, especially among infants, children and the elderly. The only exception was Chilean men aged 20–39, for whom inequality in mortality remained persistently high. Robust economic growth and targeted health interventions in the 1990s contributed to declining mortality rates and mortality inequality. From 2000 to 2010, efforts to expand safety nets and improve health-care access continued, with a greater impact on adults aged 49 years and above. Despite these advances, child mortality remains significantly higher than in developed countries, and the increasing number of female suicides in younger age groups represents a concerning trend.
Keywords: 330; Chile; income inequality; mortality inequality; welfare